Tindakan Pencegahan Efek Masker N95 yang Dilakukan Tenaga Kesehatan Selama Pandemi COVID-19 - M. Rusli; Kadek Ayu Erika; Yuliana Syam (Journal of Telenursing (JOTING), 2022)
This study aims to identify the actions of health workers in preventing the effects of N95 masks. The research method used is literature review through electronic databases and websites, namely Pubmed, Proquest, ScienceDirect and Wiley. The results showed that from 9 research articles, there were articles that reported that the use of bandages was effective in preventing injury and providing comfort, there were also articles that wrote no harm but caused discomfort and there were those who reported more pressure injuries with the use of bandages than those who did not use a dressing. In conclusion, preventive measures by using sanitary napkins when wearing an N95 mask can be applied, although further research is still needed to determine its effectiveness. Keywords: Effect, N95 Mask, Pads, Action